Filtration Efficiency of Air Conditioner Filters and Face Masks to Limit Exposure to Aerosolized Algal Toxins - Cassandra J. Gaston; Haley M. Royer; Raymond J. Leibensperger; Daniela Maizel; Kaycie B. Lanpher; Helena Solo-Gabriele; Larry E. Brand; R. Grace Zhai; Alberto J. Caban-Martinez; Kimberly J. Popendorf (Aerosol and Air Quality Research)
Abstract Harmful algal blooms (HABs) can generate toxins that can be aerosolized and negatively impact human health through inhalation. HABs are often found in waterways near residences, therefore, aerosolized HAB toxins can potentially affect both indoor and outdoor air quality. Given that HABs are predicted to increase worldwide, effective mitigation strategies are needed to prevent the inhalation of aerosolized HAB toxins. In this work, we characterized both the particle filtration efficiency using particle sizing instruments as well as the mass concentration of different congeners of aerosolized microcystin (MC) toxins that penetrate through commercially available face masks and air conditioner (AC) filters. Particles were generated from cultures of the toxin-producing cyanobacteria Microcystis aeruginosa. Hydrophobic congeners of microcystin including MC-LF and MC-LW were enriched in aerosols compared to water, with MC-LR being the most abundant, which has implications for the toxicity of inhalable particles generated from HAB-contaminated waters. Particle transmission efficiencies and toxin filtration efficiencies scaled with the manufacturer-provided filter performance ratings. Up to 80% of small, microcystin-containing aerosols were transmitted through AC filters with low filter performance ratings. In contrast, both face masks as well as AC filters with high filter performance ratings efficiently removed toxin-containing particles to below limits of quantification. Our findings suggest that face masks and commercially available AC filters with high filtration efficiency ratings are suitable mitigation strategies to avoid indoor and outdoor air exposure to aerosolized HAB toxins. This work also has relevance for reducing airborne exposure to other HAB toxins, non-HAB toxins, pathogens, and viruses, including SARS-CoV-2, the virus responsible for the COVID-19 pandemic.